A Survey of Palestine, [prepared by the British Mandate for UN prior to proposing the 1947 partition plan] - United Nations. General Assembly; Anglo-American Committee of Inquiry on Jewish Problems in Palestine and Europe ([s.l.] [s.n.], 1945)
A Survey of Palestine was the official research prepared by Government of Palestinian (then under British military occupation/Mandate) for the United Nation Special Committee on Palestine (UNSCOP) in 1946. The below three volumes (over 1,300 pages all available below) covers all aspects of Palestinian life before Nakba such as: population, land registration and sale, agriculture, industry, immigration, industry, political parties, exports, welfare, natural resources, energy, ... etc. Since many Zionist Myths (most importantly Palestine was an empty country, and Jews made its desert bloom) have been concocted to legitimize the Zionist enterprise, we found it critical to share have been concocted to legitimize the Zionist enterprise, we found it critical to share this research with the general public. In our opinion, if you are serious about knowing the core issues of the Palestinian-Israeli conflict, then this research is a must read. We hope you enjoy this presentation and please share with friends and loved ones. We shall return.​ (www.palestineremembered.com)
https://www.palestineremembered.com/Acre/Books/Story831.html
​data pertaining to populations, landownership, and land use has been extracted from another important British Mandate publication (which had limited circulation at the time) called Village Statistics (www.palestineremembered.com) Vol. 3 is not available at the library
Includes bibliographical references and index.
Keywords: PALESTINE; MIDDLE EAST; SURVEYS; Palestine